STUDI TENTANG PENGELOLAAN PASAR TRADISIONAL PADA UNIT PASAR SURUH KABUPATEN SEMARANG - Fitriyati, Nur; Adnan, Muhammad; Yuwono, Teguh (Journal of Politic and Government Studies, 2017)
The need for good traditional market management as well as the problemsoccurring in the management of traditional markets into the background of thisresearch. Problems arise: How is the conflict of interest between the RegencyGovernment and the Village Government in the management of Suruh MarketSemarang regency? What are the social and economic impacts of conflict ofinterest between the Regency Government and the Village Government in themanagement of Suruh Market Semarang regency?The purpose of this study is to explain how the process of conflict ofinterest in the management of traditional markets is Suruh Market between theRegency Government and Village Government. In addition to describe andanalyze the impacts resulting from the conflict of interest in the management oftraditional markets, especially Suruh Market viewed from the social and economicaspects.This study uses a combined research method between qualitative andquantitative with a qualitative approach fixed as the main approach. Dataobtained through interviews and questionnaires. The data obtained from thequantitative approach through the survey is used to reinforce the facts related tothe theme and the formulation of related problems. In addition, usingTriangulation data sources to compare the results of interviews with one another.The result of the research shows that conflict of interest occurs because ofdifferent interests between parties involved. Regency Government, VillageGovernment and Traders have a mutually striving interest. Conflict of interestoccurs when the Regency Government wants to take over and manage the SuruhMarket completely but there is a rejection by the Village Government. The socialimpact that occurs is the decline in the number of traders and competition amongtraders is getting tougher. While the economic impact is a decline in the turnoverof traders.Keywords: Management, Traditional Market, Interest